Current status of KAB in health education for Chinese college students and SEM validation exploration - Zhao, Yuehui; Guan, Yangyang; Chen, Zihao; Gong, Hailin (Frontiers in Public Health, 2025)
IntroductionIn the field of health education, the KAB theory is an authoritative theoretical model worldwide; however, there is not much empirical evidence supporting its application in university health education. Therefore, the purpose of this paper is to use data from Chinese universities to test the pathways and universality of the KAB model, as well as to provide certain suggestions for future health education in universities through a situational analysis.MethodsWe used a random sampling method to conduct a questionnaire survey of 4,508 college students from 76 universities in Jiangsu Province (752 from sports majors and 3,756 from non-sports majors). We employed a self-developed four-point scale questionnaire (20 questions on health knowledge, 14 on attitudes, and 10 on behaviors), which demonstrated good reliability and validity (Cronbach’s α: 0.958–0.969). Exploratory factor analysis was conducted to extract the dimensions of attitude and behavior, and structural equation modeling (SEM) was used to verify the K → A → B theoretical pathway.ResultsCurrent status: The awareness of sexual and reproductive health was highest (89.7%–98%), while knowledge of disease prevention was the weakest (awareness of antibiotic hazards was only 57.5%); sports majors scored significantly higher in health knowledge than non-sports majors (e.g., 15.7% higher in disease prevention knowledge). In terms of behavior, the rate of developing exercise habits among non-sports majors (87.6%) was significantly lower than that of sports majors (97.9%), and only 69.6% actively consulted health issues, showing that students are hesitant to talk to their teachers. Model validation: The SEM fit indices were good (GFI = 0.972, RMSEA = 0.065), confirming three key pathways: knowledge → attitude (β = 0.42), attitude → behavior (β = 0.33), and knowledge → behavior (β = 0.55). Multi-group analysis showed that the model has universality across genders and majors, but the pathway from knowledge to behavior was stronger for males (β difference +0.11), while the pathway from attitude to behavior was more pronounced for females (β difference +0.09).DiscussionThe KAB model is applicable to the college student population, where health knowledge not only directly influences behavior (β = 0.55) but also has an indirect effect through attitude. We need to focus more on teaching disease prevention, such as the hazards of antibiotics, design behavioral intervention courses for non-sports majors, and we should also notice that students are less willing to seek health advice in person. The study validates the universality of the KAB theoretical pathway, giving solid proof for health education in universities.